Gene expression programming function mining based upon grid - DENG Song1; WANG Ru-chuan1 (Tongxin xuebao)
The concepts of success rate of function mining,weak correlation and merger of function consistency were proposed.On the basis of these,gene expression programming function mining based on grid（GEPFM-Grid） was put forward.By extensive experiment of GEPFM-grid and other traditional algorithms,the results show that success rate of function mining and convergent speed of GEPFM-grid is obviously improved,and that consumptive time is less.